Fe-based bulk metallic glasses : understanding the influence of impurities on glass formation - Stoica, Mihai (Springer, 2017)
Mihai Stoica investigates in details the glass formation of two model alloys, [(Fe0.5Co0.5)0.75B0.2Si0.05]96Nb4 and Fe74Mo4P10C7.5B2.5Si2. More than 20 master alloys using different raw materials were prepared. Besides the typical calorimetry and X-Ray diffraction, magnetic measurements were employed to analyze the amorphicity degree of the sample. Two new bulk metallic glass-forming alloy compositions are designed and possible preparation routes are proposed. Contents Theoretical aspects, Experimental Details and Particularities [(Fe0.5Co0.5)0.75B0.2Si0.05]96Nb4 Alloy A New Model Alloy: Fe74Mo4P10C7.5B2.5Si2 Developing New Bulk Metallic Glasses Starting from Fe77.5P12.5C10 Composition Target Groups Scientists and students in the field of material sciences, physics and engineering Practitioners in the industrial field of material sciences About the Author Dr. Mihai Stoica is a Scientist in the group of Metal Physics and Technology, ETH Zurich, Switzerland. Former leader of the 'Solidification Processes and Complex Structures' group at the Leibniz Institute for Solid State and Materials Research Dresden, Germany, M. Stoica holds a PhD Degree in Physics. His scientific interests are focused on preparation and characterization of bulk metallic glasses, as well as on their mechanical and magnetic properties. Since October 2013 he is Visiting Associate Professor at Politehnica University Timisoara, Romania, where he accomplished the Habilitation in Materials Engineering in October 2015.
Keywords: Metallic glasses.; elektronické knihy; electronic books